Monitoring the apical growth characteristics of hairy roots using non‐invasive laser speckle contrast imaging. Issue 3 (13th December 2021) - Schott, Carolin; Bley, Thomas; Walter, Thomas; Brusius, Janis; Steingroewer, Juliane
Abstract: Hairy roots are used to produce plant agents and additives. Due to their heterogeneous structure and growth characteristics, it is difficult to determine growth‐related parameters continuously and in real time. Laser speckle contrast analysis is widely used as a non‐destructive measurement technique in material testing or in medical technology. This type of analysis is based on the principle that moving objects or particles cause fluctuations in stochastic interference patterns known as speckle patterns. They are formed by the random backscattering of coherent laser light on an optically rough surface. A Laser Speckle Imager, which is well established for speckle studies of hemodynamics, was used for the first time for non‐invasive speckle measurements on hairy roots to study dynamic behavior in plant tissue. Based on speckle contrast, a specific flux value was defined to map the dynamic changes in the investigated tissue. Using this method, we were able to predict the formation of lateral strands and to identify the growth zone in the apical root region, as well as dividing it into functional regions. This makes it possible to monitor physiological processes in the apical growth zone in vivo and in real time without labeling the target structures.